Software architecture hour. (O'Reilly Media, Inc., 2022)
Microservices can greatly benefit your systems--but they bring along their own host of problems. If you're getting started with microservices, Sam Newman's Building Microservices offers a wealth of practical advice for building, managing, and scaling microservices architectures. Or you could just hear it from him directly. Join us for a special conversation on microservices with Neal Ford and Sam Newman. They'll discuss what changed between the first and second editions of Building Microservices, what next-generation microservices will look like, and the right way to build distributed systems. Then they'll dive into some patterns for building, organizing, observing, and operating microservices in the real world. Neal and Sam will spend a few minutes covering the trends in microservices that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Get practical advice on building, organizing, observing, and operating microservices See what's coming next with software architecture This recording of a live event is for you because... You want to learn about microservices-style architectures. You're looking for ways to improve your architecture. Recommended follow-up: Read Building Microservices, second edition (book) Read Monolith to Microservices (book) Read Fundamentals of Software Architecture (book) Read Software Architecture: The Hard Parts (book) Attend Software Architecture Superstream: Soft Skills Are the Hardest Part (live online event, June 22).